Role of Ovarian Hormones in Psychological Stress-induced Oxidative Organ Damage in Rats - YEGEN, BERRAK (AVES PRESS LTD, 2016)
Objective: Stress response varies with respect to gender via the hypothalamic-pituitary-gonadal axis. We aimed to investigate the effect of ovarian hormone deficiency on psychological stress response and oxidative damage. Methods: Female Sprague Dawley rats (250-300 g, n=56) were divided as control, sham, and ovariectomy (OVX) groups. Sham operation or surgical OVX were conducted under anesthesia. After 60 days, the rats were placed in a special chamber to induce psychological stress by electric shock and were kept in the same chamber for 30 min on the following 3 days. Glucocorticoid receptor antagonist RU-486 (10 mg/kg), oxytocin receptor antagonist atosiban (1 mg/kg), or saline was intraperitoneally administered 10 min before stress exposure. After the hole-board anxiety test, the rats were decapitated on the 4th day; tissue and blood samples were obtained. Results: Psychological stress increased cortisol levels in the RU-486-administered group, while cortisol levels were decreased in the atosiban-administered group. Serum interleukin (IL)-1 ss levels, but not TNF-alpha levels, were increased by inducing stress. Stress increased oxidative damage in the stomach, colon, and brain of ovariectomized rats (p<0.05-0.001), while atosiban partially reversed and RU-486 exaggerated oxidative damage. GSH levels that were depleted because of stress were partially replenished by administering atosiban; however, RU-486 had no effect on GSH levels. Conclusion: Although the absence of ovarian hormones during psychological stress had no effect on cortisol or anxiety levels, changes in cytokine levels and oxidative tissue damage were observed.
Keywords: Hypothalamopituitary-adrenal axis; hypothalamopituitary gonadal axis; glucocorticoid receptor; atosiban; oxytocin